A Transitivity Analysis of Students’ Writing Recount Text Based on Systemic Functional Linguistics at SMP Negeri 27 Medan - Nayla Firzanah; Mira Mailani; Stefani Angelica Sinambela; Jelita Purnamasari Gulo (CV Edu Tech Jaya, 2026)
This study analyzed the types of transitivity processes and the realization of transitivity processes found in students’ recount text writing at SMP Negeri 27 Medan. The study was conducted because many students still experienced difficulties in expressing ideas and organizing experiences effectively in recount texts. This research aimed to identify the types of transitivity processes used by students and to describe how the processes were realized through process, participant, and circumstance elements in clauses. This study applied a descriptive qualitative method. The data of this research were clauses taken from five recount texts written by seventh-grade students of SMP Negeri 27 Medan. The data were analyzed based on the transitivity system in Systemic Functional Linguistics proposed by M. A. K. Halliday and Christian M.I.M. Matthiessen. The findings showed that six types of transitivity processes were found in the students’ recount texts, namely material process, mental process, relational process, verbal process, behavioral process, and existential process. Material process became the dominant process because students mostly described physical activities and past experiences through action verbs. In addition, the realization of transitivity processes was represented through process, participant, and circumstance elements. The findings indicate that students were able to represent experiences and meanings through language in recount text writing, although most of the texts still used simple sentence patterns and limited vocabulary. This study is expected to contribute to English language teaching, especially in improving students’ writing ability through the application of Systemic Functional Linguistics.